Relationship between social participation and stigma in people affected by leprosy: A cross-sectional study in northeastern Brazil - Lima, Marize Conceicao Ventin; Arruda, Gustavo Aires de; Alves, Maria Geórgia Torres; Brandão Neto, Waldemar; Albuquerque, Cássia Cibelle Barros de; Nascimento, Raphaela Delmondes do; Pereira, Emanuela Batista Ferreira e; Valença, Marilia Perrelli; Moura dos Santos, Danielle Christine (Belitung Raya Publisher - Belitung Raya Foundation, 2026)
Background: Leprosy remains a persistent public health challenge, especially in endemic areas, where its historical association with stigma continues to harm social participation and psychosocial well-being. Understanding how stigma affects social participation across different life areas is crucial for developing effective care and public health strategies. Objective: To examine the association between stigma and social participation across different domains among people affected by leprosy. Methods: A cross-sectional, quantitative study was conducted in 2019 with 97 individuals affected by leprosy followed at eight municipal reference units in Recife, Pernambuco, Brazil. Sociodemographic, environmental, and clinical data were collected using structured instruments and medical records. Stigma was assessed using the Explanatory Model Interview Catalogue (EMIC), and social participation was evaluated using the Participation Scale (PS). Data were analyzed using descriptive statistics, Spearman’s correlation, chi-square tests for linear trend, and effect size estimation using Cramér’s V. Statistical significance was set at p <0.05. Results: A total of 53.6% of participants presented some degree of restriction in social participation. The mean stigma score was 16.63 (SD = 8.53), and the mean participation score was 16.58 (SD = 13.62). A statistically significant, low-magnitude correlation was observed between stigma and participation restriction scores (Spearman’s rho = 0.25; p = 0.016). Categorical analysis demonstrated a significant linear association between higher stigma tertiles and greater participation restriction (χ² for trend, p = 0.022), with a low overall effect size (Cramér’s V = 0.20; 95% CI: 0.10–0.36). Moderate effect sizes were observed in specific participation domains, including religious and community activities (Cramér’s V = 0.24; p = 0.02), visiting other people in the community (Cramér’s V = 0.26; p = 0.01), and perceived respect within the community (Cramér’s V = 0.29; p = 0.04). Conclusion: Stigma was significantly associated with restricted social participation among people affected by leprosy. Although the overall association showed low magnitude, moderate and statistically significant associations were observed in key social domains. These findings support the inclusion of stigma and social participation assessments in routine leprosy care and highlight the need for integrated clinical, psychosocial, and community-based nursing and health interventions aimed at reducing stigma and promoting social inclusion.